The importance of the independence of the Iraqi State Council - Salih, Omar; Almosawi, Ali (Journal of Legal Sciences, 2022)
The State Council is always the trusted advisor to the administration in matters emerging, and the trusted repository of its secret. It assists the administration in the process of developing the appropriate formula for draft laws, regulations, and instructions, in order to make them lead to their intended goal, through its advisory function.    He is rightly considered the symbol of administrative justice and its faithful habitat. With what it lays down the principles of legality, and with its prestige, strength, integrity, and well-established traditions, it can always confirm the guarantee of its aspired independence, and that the rule of law has a tool for its advancement, not separated from its conscience, but rather interacting with it. To guarantee its advancement to broader horizons than upholding the values ​​of truth and the elevation of the word of law.   He is the government's advisor and the drafter of its legislation. He carries out judicial oversight over the administration's actions if the rights and freedoms of individuals are abused, until the State Council has become the bulwark of legality and the protector of rights and freedoms.